Induction of luteolysis in mares utilizing a micro-dose of prostaglandin F-2 alpha in the sacral lumbar space - Alvarenga, Marco Antonio [UNESP]; Ferreira, J. P C [UNESP]; Meira, Cezinande de [UNESP]; Luna, Stélio Pacca Loureiro [UNESP]; Burns, P. J. (William E Jones Dvm, 1998)
An experiment was conducted to examine the luteolytic effectiveness of using low or micro doses of PGF2α when administered at the BAI HUI acupuncture point, which is frequently used to treat ovarian disturbances in veterinary acupuncture. The results indicate that PGF2α given at a very low micro dose of 0.5 mg (one tenth the conventional recommended dose) administered at the BAI HUI acupuncture point located at the sacral lumbar space is equally effective at inducing luteolysis in mid-luteal phase mares as conventional PGF2α i.m. treatment using a tenfold higher dose. Therefore, based on the results of the present study, we suggest that the BAI HUI sacrai lumbar route somehow provides an extremely efficient pathway for the drug to the ovarian level.